Factors Influencing Nurse Interns’ Competence in Physical Assessment for Adult Patients - Nelly Kiplagat; Damaris Ochanda; Mary Kipmerewo (Evidence-Based Nursing Research)
Context: Physical assessment is essential to the overall health assessment, constituting the nursing process's first phase. The physical assessment competence of nurse interns has been observed as insufficient in evaluating and solving patients' health problems in the clinical environment. This insufficiency has negatively influenced their ability to make better clinical decisions for patients, thus contributing to poor quality of patient care.